A nightmare on Elm Street 5, The dream child & Freddy's dead: the final nightmare [videorecording (DVD)]. - Englund, Robert, 1947-; Wilcox, Lisa, 1964-; Hopkins, Stephen; Craven, Wes; Bohem, Leslie; Talalay, Rachel, 1958-; Zane, Lisa; Greenblatt, Shon; Deane, Lezlie; Kotto, Yaphet (New Line Home Entertainment, 2017)
(A nightmare on Elm Street 5) Unable to overpower the dream master who vanquished him in A Nightmare on Elm Street 4, Freddy haunts the innocent dreams of her unborn child and preys upon her friends with sheer horror. Will the child be saved from becoming Freddy's newest weapon or will the maniac again resurrect his legacy of evil?